Empowering UDI-Barabai Fermented Peanut MSMEs through Local Product Education, Storytelling, and Digital Collaboration - Zulfikar, Rizka; Herawati, Ana Sofia; P, Purboyo; Yulianti, Farida; Mayvita, Prihatini Ade; A, Azahraty; Sanjaya, Fanlia Adiprimadana; S, Syahrani (Nanggroe: Jurnal Pengabdian Cendikia, 2026)
Kacang Jaruk is a traditional fermented food from Barabai, Hulu Sungai Tengah, South Kalimantan, possessing high cultural value but limited market performance due to weak branding, packaging, and digital marketing. This community service aimed to empower Kacang Jaruk Udi Barabai MSME through the “3 Pillars of Growth: Product-Story-Digital” Model. Using Participatory Action Research with a Pentahelix approach from March–June 2026, interventions included: 1) Local product education through GMP SOP development and PIRT legalization; 2) Storytelling via new packaging, QR Codes, and the “Satu Rasa Seribu Cerita” content series; 3) Digital collaboration with micro-influencers, resellers, and marketplace onboarding. Results showed production capacity increased from 15 kg to 40 kg/week, selling price rose by 46.7%, revenue grew 85% with 62% from online channels, and local employment was created. This model proves that integrating cultural values, brand narrative, and digital technology can elevate traditional food MSMEs from survival to growth. The approach is replicable for other culture-based local MSMEs.